Indiana Secondary School Athletic Directors Perceptions of Athletic Training Services and Influences on Hiring Athletic Trainers - Greffly, Thomas; Rivera, Matthew; Eberman, Lindsey (Bowling Green State University, 2021)
Purpose: The purpose of this investigation was to examine ADs perceptions on satisfaction of current care provided, factors influencing the hiring of ATs, and the roles and responsibilities of ATs. Methods: We used a mixed methods design with an online survey (Qualtrics®, Provo, UT), which we distributed to Indiana secondary school ADs (n = 410) with publicly available emails. The survey remained open for 5 weeks with reminder emails sent weekly. We used a panel (n=2) with experience in survey research and/or the secondary school setting. The survey included both quantitative (7 items) and qualitative (8 items) data. Participants were asked to share their perceptions on the roles/responsibilities of ATs as well as experiences with the challenges, barriers, and benefits of hiring ATs in open-ended questions. We used Kruskal-Wallis one-way ANOVAs to compare employment status, type of employer, and school size on satisfaction. We coded the open-ended responses using inductive coding with multi-analyst triangulation and auditing to establish trustworthiness. Results: We identified significant differences relative to employment status of the AT on satisfaction with overall care, whereby those with full-time athletic training services were more satisfied with care than those with per-diem, part-time services (p=0.010). When participants were asked about factors influencing the decision to provide services ADs reported liability, cost, and workload as major considerations. Conclusions: Consistent with previous research, financial challenges continue to play a role in the hiring of ATs in the secondary school setting, participants also identified the benefits of ATs in promoting safety, reducing liability, as well as the increased workload and cost. Access to qualified athletic healthcare continues to be a public health concern in America and all stakeholders should reconsider how to offer both a comprehensive athletics program and the healthcare needed to ensure safety in that participation.